FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN KEBERHASILAN PEMBERIAN ASI EKSKLUSIF OLEH IBU BEKERJA DI KOTA DENPASAR - Dewi, Made Ayu Puspa; Puspita, Luh Mira; Eva Yanti, Ni Luh Putu (Coping: Community of Publishing in Nursing; Vol 11 No 2 (2023): April 2023DO - 10.24843/coping.2023.v11.i02.p08, 2023)
A working mother is frequently facing barriers in breastfeeding their babies. Several barriers in breastfeeding faced by the working mothers are the long duration of work, the lack of opportunities and support provided by the workplace for mothers to do the breast milk due to the unavailability of breastfeeding facilities such as lactation rooms, and the lack of knowledge of working mothers regarding lactation management. This study aims to determine the factors associated with the success of exclusive breastfeeding by working mothers in Denpasar City. This study was quantitative correlative research by using a cross-sectional   design and purposive sampling technique. Data collection was carried out on 97 respondents who visited Puskesmas 1 Denpasar Utara, Puskesmas 1 Denpasar Timur, Puskesmas 2 Denpasar Barat, and Puskesmas 2 Denpasar Selatan. Data collection used knowledge, availability of lactation facilities at work, and husband's support questionnaires. The eta   test   and contingency coefficient were used for the data analysis.   The results showed that there was no correlation between age (p=0,08), parity (p=0,132), baby's gender (p=0,501), socioeconomic status (p=0,111), type of mother's occupation (p=0,70), knowledge (p=0,338), availability of lactation facilities (p=0,3), and husband's support (p=0,180) with exclusive breastfeeding. However, distance (0,019) and duration of work (p=0,044) were associated with exclusive breastfeeding (p<0,05). In conclusion, there is a relationship between distance and duration of work seem as predictors of exclusive breastfeeding by working mothers in Denpasar City. It is expected to increase knowledge of working mothers about the management of expressed breast milk, thus the exclusive breastfeeding can be achieved.